2017
DOI: 10.1039/c6ra25413f
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of manganese–cerium doped metal–organic frameworks prepared via impregnation and in situ methods in the selective catalytic reduction of NO

Abstract: aMn and Ce were loaded on metal-organic frameworks (MOFs) via impregnation and in situ doping methods. The catalytic capacities of the obtained composite materials were evaluated in the selective catalytic reduction (SCR) of NO. The existing form of Mn-Ce in the MOF originates from different doping methods and its effect on the catalytic performance was investigated. Mn-Ce introduced by impregnation was deposited on the surface of the MOF and exhibited high catalytic efficiency of more than 98% from 200 C to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…The introduction of Mn and Ce to UiO-67 by impregnation method enabled the great redox property of MnCe@MOF catalyst, which exhibited better NH 3 À SCR activity than MnCe-MOF catalyst prepared by in-situ doping method. [106] Shi et al reported that the introduction of Cu + species into the framework of MIL-100(Fe) via a hydrothermal method. could further boost the NH 3 À SCR activity of MIL-100(Fe).The newly formed activity sites and the interaction between Cu + species and Fe sites were the main reasons for the improved activity.…”
Section: Metal Organic Framework (Mofs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of Mn and Ce to UiO-67 by impregnation method enabled the great redox property of MnCe@MOF catalyst, which exhibited better NH 3 À SCR activity than MnCe-MOF catalyst prepared by in-situ doping method. [106] Shi et al reported that the introduction of Cu + species into the framework of MIL-100(Fe) via a hydrothermal method. could further boost the NH 3 À SCR activity of MIL-100(Fe).The newly formed activity sites and the interaction between Cu + species and Fe sites were the main reasons for the improved activity.…”
Section: Metal Organic Framework (Mofs)mentioning
confidence: 99%
“…The loading method also has a significant effect on the MOFs supported catalyst for NH 3 −SCR. The introduction of Mn and Ce to UiO‐67 by impregnation method enabled the great redox property of MnCe@MOF catalyst, which exhibited better NH 3 −SCR activity than MnCeMOF catalyst prepared by in‐situ doping method [106] . Shi et al.…”
Section: The Design Of Spatial Confined Architectures For Nh3−scr Catmentioning
confidence: 99%
“…So far as we know, only a few studies have examined the interaction between different linkers in MOFs and energy transfer between them leading to photocatalytic activities [25,32,[34][35][36]. It is known that Ce can promote energy transfer due to its low-lying empty 4f orbitals and act as active sites for H 2 evolution [37][38][39][40][41][42]. In this work, we introduced Ce 4+ into UiO-67 to form UiO-67-Ce by replacing some bpdc of UiO-67 with bpydc-Ce (namely, a complex formed by bpydc coordinated with Ce 4+ ) and demonstrated that the photocatalytic H 2 evolution rate is greatly enhanced over UiO-67-Ce than UiO-67.…”
Section: Introductionmentioning
confidence: 99%
“…High specic surface area is helpful for the adsorption performance of the catalyst. 22,35 However, as shown in Fig. 8(a) and (c), NO oxidation efficiencies increased with the total loading from 7% to 15%, which demonstrated that the loading amount or the content of active component was the main factor inuencing the catalytic activity when compared to the specic surface area.…”
Section: No Oxidation Propertiesmentioning
confidence: 89%